KINERJA DINAS KOPERASI, UKM DAN PERDAGANGAN KABUPATEN KLUNGKUNG DALAM PEMBERDAYAAN UMKM (USAHA MIKRO, KECIL, DAN MENENGAH) KERAJINAN KAIN TENUN ENDEK - Pradnyawati, Kadek Ayu Febriantini; Yudartha, I Putu Dharmanu; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2020)
ABSTRACT Endek woven fabric craft is one of the featured products in Klungkung Regency. The problems faced by MSME (Micro, Small and Medium Enterprises) Endek woven fabric craft in Klungkung Regency was mostly about business management such as capital problems, limited human resources (HR), as well as production and marketing. This research used descriptive qualitative methods and the data were collected through observation, interviews, and documentation techniques. The result of the research showed that the empowerment had not been able to run optimally and did not meet the government targets, because there were still several problems that became the obstacle factors, namely the lack of labor, there was no regeneration or renewal of facilities and infrastructure that still limited, as well as a lack of socialization in growing community interest. Keywords : Empowerment, MSME (Micro, Small, and Medium Enterprises) Endek Woven Fabric Crafts, Organizational Performance.